Pipped at the Post: Knowledge Gaps and Expected Low Parental IT Competence Ratings Affect Young Women’s Awakening Interest in Professional Careers in Information Science - Schorr, Angela (Frontiers in Psychology, 2019)
Although many jobs in today's information science allow work-life-schedules for women, they still hesitate to enter this territory. In a study based on individual interviews with N=134 students aged 14-18 years, who visited the Deutsches Museum in Munich, Germany, we collected data on the students' ICT socialization, on their self-rated ICT competence, their working knowledge of the ICT profession, and their reaction to sexist statements. To analyze more in depth, we provided the participants with two alternative forms of vocational counseling interventions designed to modify their ICT-related attitudes (information vs. robotics condition). Analyzes of variance and multiple linear regressions were administered to the data. Results: The girls in this study were socialized more than one year after the boys in using computers. While the boys received their ICT training mostly through their fathers and peers, the girls frequently had to rely on their teachers for ICT instruction. They rate their ICT competence lower than the boys. Nevertheless, both genders share a relatively high interest in the ICT professions. What’s more, the girls are less convinced that men have a natural talent for computer science. Openness towards taking up jobs in the ICT industry in the case of the boys is less dependent on their self-rated computer competence and on what they perceive their parents think about their ICT talents. In both intervention conditions, they eagerly received and processed the new information provided. The girls’ interest in an ICT career largely depends on preconditions, namely on their self-rated ICT competence, on a long-standing enthusiasm for computers, and on the degree they believe their parents are convinced of their computer competence. Unlike the more pragmatic approach of the boys, their self-doubts, especially among the academic high school girls brings about that they are still in danger to leave the field of information/computer science before having entered it. In general, the participants' responses point to a comprehensive misdirection of young women in German middle schools and academic high schools. Fortunately, this study provides a lot of evidence on how to fix this major mishap in the interest of both sexes.